2021
DOI: 10.3390/foods10030605
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Treatments for Preserving Fresh Vegetables Quality: A Critical Review

Abstract: Ozone is recognized as an antimicrobial agent for vegetables storage, washing, and processing. This strong disinfectant is now being used in the food industry. In this review, the chemical and physical properties of ozone, its generation, and factors affecting ozone processing efficiency were explained as well as recent regulatory developments in the food industry. By then selecting three vegetables, we show that ozone avoids and controls biological growth on vegetables, keeping their attractive appearance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 125 publications
0
17
0
Order By: Relevance
“…With regard to this, ozone has a reduced environmental impact compared to other chemicals employed in food processing environments and its effectiveness against a wide range of microorganisms is well documented [ 18 , 26 ]. The future possible application of this technology in food processing environments has been thoroughly reviewed in the last years [ 26 , 27 , 28 , 29 ]. However, data concerning the action of ozone on microbial biofilm are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this, ozone has a reduced environmental impact compared to other chemicals employed in food processing environments and its effectiveness against a wide range of microorganisms is well documented [ 18 , 26 ]. The future possible application of this technology in food processing environments has been thoroughly reviewed in the last years [ 26 , 27 , 28 , 29 ]. However, data concerning the action of ozone on microbial biofilm are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Although the application of ozone in several foods, and beverages, has been discussed extensively (Table 2) (Botondi et al, 2021;De Santis et al, 2021;Sarron et al, 2021;Sivaranjani et al, 2021), no review to date has F I G U R E 1 Ozone production in the atmosphere comprehensively analyzed the prospects of using this technology in wineries. Therefore, this review discussed the efficacy of the ozone treatment and a promising alternative sanitizing agent to traditional methods to prevent microbial growth in the wine industry.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables tend to be more sensitive to ozone than fruits in terms of ozone‐induced injury. Studies have demonstrated that gaseous ozone is not likely of commercial value for leafy vegetables (Sarron et al., 2021). Therefore, the present review focuses on the application of gaseous ozone on fruits.…”
Section: Introductionmentioning
confidence: 99%